COUNTRY FOCUS Micro, Small and Medium Enterprises in Indonesia - Tulus T.H. Tambunan (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
Definition and CharacteristicsIn Indonesia, the classification of enterprises is set in the Law No. 20, 2008. The criteria used are net asset value excluding land and building of business premises, and annual revenues (Table 1). Alternatively, the Indonesian Agency of Statistics (BPS) adopts the number of workers as the criteria: microenterprise (MIE): 0-4 persons; small enterprise (SE): 5-19 persons; medium enterprise (ME): 20-99 persons; and large enterprise (LE): > 99 persons.